2016
DOI: 10.1007/s00227-016-2920-0
|View full text |Cite
|
Sign up to set email alerts
|

Is metabarcoding suitable for estuarine plankton monitoring? A comparative study with microscopy

Abstract: which increased the taxonomic assignment success from 23.7 to 50.5 %. When the communities were studied along with environmental variables, similar spatial and temporal trends of taxonomic diversity were observed for metabarcoding and microscopic studies of zooplankton, but not for phytoplankton. This is most likely attributable to the lack of representative sequences for phytoplankton species in current databases. In addition, there was high correspondence in community composition when comparing abundances es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
104
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(120 citation statements)
references
References 60 publications
(76 reference statements)
5
104
0
Order By: Relevance
“…To circumvent this problem, we suggest here a method based on abundance ranks. The semiquantitative or rank-level value of metabarcoding data has been shown in several contexts (e.g., Kelly et al, 2014b;Sun et al, 2015;Abad et al, 2016;Albaina et al, 2016, Hänfling et al, 2016. Our method is expected to filter out potential biases, at the cost of partially sacrificing the quantitative information present.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…To circumvent this problem, we suggest here a method based on abundance ranks. The semiquantitative or rank-level value of metabarcoding data has been shown in several contexts (e.g., Kelly et al, 2014b;Sun et al, 2015;Abad et al, 2016;Albaina et al, 2016, Hänfling et al, 2016. Our method is expected to filter out potential biases, at the cost of partially sacrificing the quantitative information present.…”
Section: Discussionmentioning
confidence: 97%
“…Research in this field followed two different approaches, one focusing on the early detection of particular pest species (targeted or active surveillance; e.g., Ardura et al, 2015;Simpson et al, 2016), and the other involving monitoring of communities for signs of appearance of alien species (passive surveillance; e.g., Comtet et al, 2015;Zaiko et al, 2015;Abad et al, 2016;Brown et al, 2016;Xiong et al, 2016). Another side of invasion biology is the assessment of the impact of alien species on native assemblages.…”
Section: Introductionmentioning
confidence: 99%
“…However, although NGS amplicon sequencing has been in use for more than a decade (Porazinska et al, ), its methods have yet to be standardized, including for nematode communities. Additional shortcomings currently include a lack of a reliable quantification methods and the problem of PCR bias, which can result in an over‐ or under‐amplification of the DNA of certain species (Geisen, Laros, Vizcaíno, Bonkowski, & Groot, ; Kebschull & Zador, ; Tang et al, ), as well as incomplete reference databases (Abad et al, ; Holovachov, ).…”
Section: Introductionmentioning
confidence: 99%
“…Metabarcoding has facilitated studies of small multicellular organisms, either whole communities or specific groups, with marine eukaryotes being a frequent focus (Brannock & Halanych, ; Dell'Anno, Carugati, Corinaldesi, Riccioni, & Danovaro, ; Haenel, Holovachov, Jondelius, Sundberg, & Bourlat, ). It can also be used in combination with morphological analyses, as demonstrated in studies of estuarine plankton (Abad et al, ; Harvey, Johnson, Fisher, Peterson, & Vrijenhoek, ; Leasi et al, ) and nematodes (Holovachov, ; Macheriotou et al, ) in marine habitats but also diatoms and other small organisms in freshwater habitats (Keck, Vasselon, Rimet, Bouchez, & Kahlert, ; Rimet, Vasselon, A.‐Keszte, & Bouchez, ). For nematodes in soil and marine habitats, however, combined microscopy and metabarcoding investigations have been carried out only at the family level (Darby, Todd, & Herman, ; Griffiths, Groot, Laros, Stone, & Geisen, ; Holovachov, Haenel, Bourlat, & Jondelius, ; Treonis et al, ), and direct comparisons of the performances of morphological identification, barcoding, and metabarcoding at the species level are still scarce (Leasi et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…These studies use 'universal' PCR primers to amplify one or more gene regions for high throughput sequencing yielding tens of millions of sequences, which are subsequently resolved into operational taxonomic units (OTUs) that can either be matched to reference databases for identification of taxa or used for various statistical measures of biodiversity (Leray and Knowlton 2016). Metabarcoding studies of marine zooplankton have ranged from analysis of the global ocean (Bik et al 2012;de Vargas et al 2015) to studies focused on particular habitats and ecosystems, such as estuaries (Abad et al 2016), the Red Sea (Pearman and Irigoien 2015), among others. Challenges remain for quantitative analysis of taxa using metabarcoding, although recent studies have shown some correlation between OTU frequency and taxon biomass Sun et al 2015).…”
Section: Metagenetics and Metabarcodingmentioning
confidence: 99%